Пути совершенствования подготовки будуших бакалавров техногенной безопасности средствами интерактивных технологий - Evsyukova, Л. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The article analyzes the concept of «interactive learning», «interactive learning technology», the characteristics and analyzed interactive learning technology that can be used in high schools Ministry of Emergencies in training future bachelors technological security (the work in pairs, rotating (shift) triples, carousel, work in small groups (the dialogue, the synthesis of thought, a joint project), role (business) game, simulation games, method PRESS, take the position, etc.). Sight classification features interactive learning technologies: the level of application – general pedagogical and student-oriented, based on philosophy – pragmatic, the main factor in the development – psychogenic, the concept of assimilation – the associative-reflex and develop; to focus on personality structures – information and transaction.